2018
DOI: 10.1371/journal.pone.0206557
|View full text |Cite
|
Sign up to set email alerts
|

An effective “three-in-one” screening assay for testing drug and nanoparticle toxicity in human endothelial cells

Abstract: Evaluating nanoparticle (NP) toxicity in human cell systems is a fundamental requirement for future NP biomedical applications. In this study, we have designed a screening assay for assessing different types of cell death induced by NPs in human umbilical vein endothelial cell (HUVEC) culture. This assay consists of WST-8, LDH and Hoechst 33342 staining, all performed in one well, which enables an evaluation of cell viability, necrosis and apoptosis, respectively, in the same cell sample. The 96-well format an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…32 Zinc oxide NPs were observed to be toxic (450%) at 50 mg mL À1 in human aortic ECs, 34 human cardiac microvascular ECs 35 and in HUVECs; 36,37 all these results are in good accordance with the 60% toxicity observed in our study for ECs derived from iPSCs. SiO 2 NPs have also been reported to induce toxicities from 20 to 60% in HUVECs for NP concentrations between 50 and 75 mg mL À1 , 38 while Ag NPs have been reported to induce toxicity in rat brain microvessel ECs 49 and to demonstrate anti-angiogenic properties. 50 It is possible that the higher toxicity of Ag NPs against HGPS-iPSC ECs, as compared to that of N-iPSC ECs, is related to a decrease in the antioxidative stress response program in HGPS-iPSC ECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Zinc oxide NPs were observed to be toxic (450%) at 50 mg mL À1 in human aortic ECs, 34 human cardiac microvascular ECs 35 and in HUVECs; 36,37 all these results are in good accordance with the 60% toxicity observed in our study for ECs derived from iPSCs. SiO 2 NPs have also been reported to induce toxicities from 20 to 60% in HUVECs for NP concentrations between 50 and 75 mg mL À1 , 38 while Ag NPs have been reported to induce toxicity in rat brain microvessel ECs 49 and to demonstrate anti-angiogenic properties. 50 It is possible that the higher toxicity of Ag NPs against HGPS-iPSC ECs, as compared to that of N-iPSC ECs, is related to a decrease in the antioxidative stress response program in HGPS-iPSC ECs.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Regarding NP28, the results are also in accordance with those reported in the literature for HUVECs exposed for 24 h, with toxicities ranging from 20 to 60% for 50 and 75 mg mL À1 SiO 2 concentrations, respectively. 38 NPs showed a differential toxic effect against both types of ECs. HGPS-iPSC ECs were more sensitive to NP13, NP18, NP22, NP26 and NP29 NPs as compared to N-iPSC ECs (Fig.…”
Section: Vascular Screening Of Nps In a 2d Modelmentioning
confidence: 95%
“…More importantly, ZnO NPs significantly increased intracellular ROS showing a stronger cellular cytotoxicity than that of Ag and TiO 2 NPs. In another case, Filipova et al (2018) reported a "three-in-one" screening assay to test the toxicity of three kinds of NPs for human umbilical vein endothelial cells. The three NPs are silica NPs (7-14 nm), superparamagnetic iron oxide NPs (8 nm), and carboxylated multiwall carbon nanotubes (60 nm), all of which were tested at the same concentration of 100 µg/ml.…”
Section: Biosafety Concerns Of Npsmentioning
confidence: 99%
“…Their HTS setup included assays for cellular membrane permeability by propidium iodide (PI) uptake, intracellular calcium flux by Fluo4 fluorophore, reactive oxygen species (ROS) production by MitoSox Red fluorophore, and mitochondrial membrane potential by 5,5 0 ,6,6 0 -tetrachloro-1,1 0 ,3,3 0 -tetraethyl-benzamidazolocarbocyanin iodide (JC-1) fluorophore. 26 More recently, Filipova et al 27 suggested a "three-in-one" screening assay for NP toxicity, which could be scaled up for high-throughput testing. Their screening assay, however, consisted of the WST-8 tetrazolium salt assay, LDH assay, and Hoechst 33342, of which the WST-8 and LDH assays showed interference with carbon-based NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Their screening assay, however, consisted of the WST-8 tetrazolium salt assay, LDH assay, and Hoechst 33342, of which the WST-8 and LDH assays showed interference with carbon-based NPs. 27 It would have been valuable if the authors had assessed all types of interference mechanisms present instead of just only one mechanism. Several other HTS screening programs have also been devised consisting of the DNA intercalating dye, Hoechst 33342, to assess cell number and nuclear size, JC-1 dye to assess perturbation of mitochondrial membrane potential, Fluo4, and PI.…”
Section: Introductionmentioning
confidence: 99%